Observations upon a paper on poor relief, by Dr. Dowling of Tipperary - Haughton, James (Dublin Statistical Society, 1862)
The essay now read seems to me to contain much suggestive matter to thoughtful men ? much that should make us pause and seriously consider the consequences of introducing into our country a more general system of out-door relief than is now administered. If, on the one hand, some real objects of benevolence are subjected by the workhouse test to hardship, on the other is there not just ground of alarm lest any considerable relaxation of it should be followed by such a general demoralization of our poor as must prove infinitely more distressing in its consequences ? I fear such would be the result, and I am therefore disinclined to out-door relief, except in the case of orphan children; and I look upon the separation of children under 8 or 10 years old from their parents as a practice which should not be continued. The following particulars relative to out-door relief in other places will, I hope, prove interesting to our society.
Read Monday, 15th April, 1861
Keywords: Poor relief; Pauperism; 314.15